Stepwise measurement procedure for the characterization of large‐area photovoltaic modules. (16th June 2015) - Rapp, Christoph; Steiner, Marc; Siefer, Gerald; Bett, Andreas W.
Abstract: In this paper, we present an indoor measurement procedure for characterizing the electrical performance of large aperture photovoltaic modules. Because of the fact that sun simulators, especially for concentrator photovoltaic applications, are strongly limited in the size of the uniformly illuminated area, we developed a measurement procedure that allows characterizing modules with a larger aperture area than the aperture provided by the sun simulator. The procedure is based on the concept of stepwise illumination of the module area and measurement of the corresponding I–V curves—without the need to contact the subunits directly. Using the additionally measured dark I–V curve of the module, the characteristic I–V curve of the full module can be calculated. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Sun simulators often are strongly limited in the size of the uniformly illuminated area. Therefore, a measurement procedure that allows characterizing modules with a larger aperture area than the aperture provided by the sun simulator is presented. The procedure is based on the concept of a stepwise illumination and measurement of the module; with a subsequent calculation, the characteristic I–V curve of the full module can be calculated.